2015
DOI: 10.1117/12.2076751
|View full text |Cite
|
Sign up to set email alerts
|

Sample to answer visualization pipeline for low-cost point-of-care blood cell counting

Abstract: We present a visualization pipeline from sample to answer for point-of-care blood cell counting applications. Effective and low-cost point-of-care medical diagnostic tests provide developing countries and rural communities with accessible healthcare solutions [1], and can be particularly beneficial for blood cell count tests, which are often the starting point in the process of diagnosing a patient [2].The initial focus of this work is on total white and red blood cell counts, using a microfluidic cartridge [3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The results of this work show a significant improvement in comparison to the first iteration microfluidic device 16 and previous version of the experimental setup, 17 where the percentage variations from the reference results were far removed from the acceptable CLIA-88 ranges.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The results of this work show a significant improvement in comparison to the first iteration microfluidic device 16 and previous version of the experimental setup, 17 where the percentage variations from the reference results were far removed from the acceptable CLIA-88 ranges.…”
Section: Discussionmentioning
confidence: 72%
“…15 The initial focus of this work is on total white and red blood cell counts, using a microfluidic cartridge for sample processing. The results using the first iteration microfluidic device 16,17 showed that the most simple-and thus low-cost-approach for microfluidic component implementation was not adequate compared with techniques based on manual cell counting principles. An improved microfluidic design has been developed to incorporate enhanced mixing and metering components, which together with this work provides the foundation on which to successfully implement automated, rapid, and lowcost blood cell counting tests.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the ability to report consistent signal intensities regardless of the variation in loading sample volume (Figure S3 of the Supporting Information) can be a useful feature for on-site monitoring purposes, where users may load imprecise volume of samples with tools such as disposable transfer pipets. Although the current format requires loading of several reagents before the experiment, this process can be further simplified by storing them in blister packs and bursting them open prior to use. , Such integration is expected to further simplify the assay and make it more suitable for on-site applications by a wide range of users.…”
Section: Results and Discussionmentioning
confidence: 99%